FUNGAL DISEASE OF VEGETABLE OF YOUR LOCALITY - MITHILESH KUMAR SINGH (International Journal of Multidisciplinary Research and Studies, 2020)
Aim of this paper was to give an overview of fungal diseases prevailing on the most common vegetables grown in Novi Sad area. For investigation, lettuce and spinach grown in a greenhouse and in open garden were chosen. In greenhouse, optimal conditions for growing lettuce and spinach were maintained, which at the same time favour the development of fungal diseases. The vegetables grown in a protected suburban open garden were more problematic considering fungal diseases. In this chapter, the prevention of fungal diseases was emphasized to avoid drastic chemical treatment or minimize its application. The adequate prevention in greenhouse is a good ecological measure. Lettuce, spinach, greenhouse, fungal disease, fungus, Vegetables are highly significant elements in human nutrition. Because of fungal assault, the nutritional content of healthy vegetables may be changed, and in certain cases, fungus can develop particular mycotoxins in them, rendering them unfit for human consumption and rendering them inedible. Crops of leafy vegetables are developed for their veggie as well as for potential therapeutic uses (Naik, 1998). Leafy vegetables offer the highest proportion of nutrients to calories of any dietary group. The vitamins A, B, C, E, and K that are found in substantial amounts in greens. Calcium, magnesium, iron, and potassium are just few of the minerals that may be found in abundance in these foods.